Nuclear Symmetry Energy and Hyperonic Stars in the QMC Model - Stone, Jirina R.; Guichon, Pierre A. M.; Thomas, Anthony W. (Frontiers in Astronomy and Space Sciences, 2022)
The nuclear symmetry energy, together with the other saturation properties of symmetric nuclear matter, plays an important role in low energy nuclear structure of terrestrial systems, as well as astrophysical objects. In particular, its density dependence, both in sub- and supra-saturation regions in high density matter in neutron stars, is of utmost significance and has been a subject of active research for decades, usually within a mean-field framework. We report results obtained using the latest version of Quark-Meson-Coupling Model (QMC-A) with just three \jrs{variable} parameters, the baryon-meson coupling constants in free space. It is shown that these parameters can be determined directly using \jrs{nuclear matter (NM) properties at saturation; two parameters of symmetric nuclear matter (SNM), the baryon number density and the energy per particle, and the symmetry energy coefficient of asymmetric nuclear matter (ANM). The effects of uncertainties in the these parameters and propagation of these uncertainties through the calculation of properties of dense hyperonic matter and cold neutron stars are demonstrated. This approach leads to new limits on both the NM parameters and the QMC coupling constants}. The results, which exploit the unique features of the QMC model, are discussed and future prospects are outlined. \